A Performance Appraisal of Madhya Pradesh State Forest Development Corporation through Accounting Ratios - Seth, V. K.; Kohli, I. S.; Jain, C. S. (Indian Forester, 1978)
Periodical appraiaals of the performance of an organisation are not only desirable, but are absolutely essential to ensure its growth along healthy lines. A Company is not only an earning concern, but also an institution for instilling confidence amongst its creditors and shareholders and in the community in general. Although there are a number of aspects to the working of an organisation, profit is a fairly precise device to measure the effectiveness of its policies' and thus provide a guide to the future. Profits, not prophets, can foretell the future. This study of tbe performance of the Madhya Pradesh State Forest Development Corporation Ltd. Over a three year period, while briefly dealing with achievement of physical targets, mainly concerns itself with the performance of the Corporation in financial terms, The figures considered in the study for the first two years are those based on actuals as per audited accounts, while those for the third year (july 1977 to June 1978) are as per budget estimates. For the purpose of this study, the technique used is Trend Analysis, i.e. a study of trends of events or business operations as revealed through financial ratio analysis over this period. Financial judgements have to be based not only on the earning capacity of a concern but also on whether it has a sound base of properly proportioned assets and liabilities that can sustain it through ups and downs of business flactuations. The ratio of current assets to current liabilities for all the years is maintained at 1.9 : 1 and is quite satisfactory according to the orthodox principles of corporate finance. Fixed Assets Ratio and Proprietary Ratios are highly satisfactory, but the ratio of dividend paid to profit earned is adverse in the third year. The gross and net profit ratios have also been quite satisfactory, in the second and third year. While the study reveals tbat tbe performance of the Corporation over this period has been quite satisfactory, it also underlines an urgent need for diversification of the activities of the Corporation and setting up of industrial units by the Corporation.